2016
DOI: 10.3847/0004-637x/832/1/69
|View full text |Cite
|
Sign up to set email alerts
|

The Sami Galaxy Survey: Galaxy Interactions and Kinematic Anomalies in Abell 119

Abstract: Galaxy mergers are important events that can determine the fate of a galaxy by changing its morphology, star formation activity and mass growth. Merger systems have commonly been identified from their disturbed morphologies, and we now can employ integral field spectroscopy to detect and analyze the impact of mergers on stellar kinematics as well. We visually classified galaxy morphology using deep images (m = -28 mag arcsec r 2 ) taken by the Blanco 4 m telescope at the Cerro Tololo Inter-American Observatory… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 93 publications
(99 reference statements)
3
18
0
Order By: Relevance
“…effective in reducing galaxy spin over a long period of time because only a small parameter space of a merger results in a spin-up during minor merger. Supporting our findings, recent observational studies have also found no clear correlation between post-merger features and spin properties (Duc et al 2015;Oh et al 2016). …”
Section: Resultssupporting
confidence: 81%
“…effective in reducing galaxy spin over a long period of time because only a small parameter space of a merger results in a spin-up during minor merger. Supporting our findings, recent observational studies have also found no clear correlation between post-merger features and spin properties (Duc et al 2015;Oh et al 2016). …”
Section: Resultssupporting
confidence: 81%
“…There is more negative scatter in the low than higher mass cases: 25 ± 3% of galaxies with log(M * /M ) < 9.5 lie below the RMS line, compared to 10% ± 1 of galaxies with log(M * /M ) > 9.5. This result is in agreement with Krajnović et al (2011), Oh et al (2016 and others.…”
Section: D Spatially Resolved Tfrsupporting
confidence: 94%
“…However, that the degree to which scatter depends on stellar mass changes between the presented TFRs (see Table 2) is indicative that it is more than a purely physical relationship, and could be at least partly a function of measurement. Oh et al (2016) demonstrated an inverse relationship between asymmetry and rotation velocity from stellar kinematics.…”
Section: Kinematic Asymmetrymentioning
confidence: 97%
“…Owing to several large IFS surveys, now it is known that even early-type galaxies mostly rotate and such rotation is tightly related to environmental density (Cappellari et al 2006;Cappellari et al 2011;Krajnović et al 2011, and many other studies). It was also revealed that direct interactions or mergers between galaxies significantly affect the position angle of galaxy rotation axis, which may result in prolate rotation (Tsatsi et al 2017;Krajnović et al 2018;Weaver et al 2018), morpho-kinematic misalignment (Barrera-Ballesteros et al 2015;Oh et al 2016), or kinematically distinct cores (Emsellem et al 2014;Krajnović et al 2015;Taylor et al 2018).…”
Section: Introductionmentioning
confidence: 99%